Isolation and Characterization of Chitosan from Kepah Shell Waste (Polymesoda erosa) Percut Sei Tuan, North Sumatera - Sitorus, Dara Indah; Ridwanto, Ridwanto (Pustaka Media Publishing, 2024)
Kepah clams (Polymesoda erosa) are one of the few aquatic animals that have a body and are protected by two cupped shells. Many people consume this shellfish meat, but many of the shells are thrown away by local people so that they only become waste. It is this shell waste that needs to be processed properly because it is known that shells are one of the fishery ingredients that contain chitin. One way to make kepah clams have a higher economic value is by isolating kepah clams into chitosan. The purpose of this study was to isolate and characterize chitosan from mussel shells and to determine functional groups using Fourier infrared (FTIR). The isolation methods used were deproteination, demineralization, depigmentation, deacetylation, and chitosan characterization. The results showed that the yield of the transformation of chitin into chitosan in cockles was 85.77% and had a brownish-white powder texture and no odor. The water content in the chitosan of the clam shells obtained was 1.53%, the ash content was 0.50%, and the degree of deacetylation obtained was 75%.